German version of the whiplash disability questionnaire: reproducibility and responsiveness - McCaskey, Michael (BioMed Central, 2013)
BACKGROUND: The Whiplash Disability Questionnaire (WDQ) poses a validated tool for the assessment of patients who experience whiplash-associated disorders. A German translation and cross-cultural adaptation was recently produced and presented high validity and internal consistency. As a follow-up, the presented study tests the translated Whiplash Disability Questionnaire’s (WDQ-G) retest reliability and responsiveness to change. METHODS: The WDQ-G was assessed on three different measurement events: first upon entry (ME1), second four days after entry (ME2), and third at discharge (ME3). Test-retest reliability data from ME1 and ME2 was analysed in a group of stable patients to obtain the intraclass correlation coefficient (ICC) and the standard error of measurement (SEM). To test the instrument’s responsiveness, WDQ-G change data were compared to concurrent instruments. The probability of each instrument, to correctly distinguish patients of the stable phase (ME1 to ME2) from patients who deemed to have improved between from ME1 to ME3, was analysed. RESULTS: In total, 53 patients (35 females, age = 45 ± 12.2) were recruited. WDQ-G scores changed from ME1 to ME2 by 5.41 ± 11.6 points in a stable group. This corresponds to a test-retest reliability of ICC = 0.91 (95% CI = 0.80–0.95) with a SEM of 6.14 points. Minimal Detectable Change, at 95% confidence, was calculated to be 17 points change in scores. Area under Receiver Operator Characteristics of the WDQ-G’s responsiveness revealed a probability of 84.6% (95% CI = 76.2%–93%) to correctly distinguish between improved and stable patients. Optimal sensitivity (73.2%) and specificity (76.2%) was established at 11-point change. CONCLUSIONS: High retest reliability and good responsiveness of the WDQ-G support clinical implementation of the translated version. The data suggest, that change in total score greater than eleven points can be interpreted as clinical relevant from a patient’s perspective. Minimal Important Change is suggested at 15 points where there is still high specificity and a 90% confidence MDC.